2019
DOI: 10.1109/lwc.2019.2939314
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning for Spectrum Sensing

Abstract: In cognitive radio systems, the ability to accurately detect primary user's signal is essential to secondary user in order to utilize idle licensed spectrum. Conventional energy detector is a good choice for blind signal detection, while it suffers from the well-known SNR-wall due to noise uncertainty. In this letter, we firstly propose a deep learning based signal detector which exploits the underlying structural information of the modulated signals, and is shown to achieve the state of the art detection perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
71
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(71 citation statements)
references
References 14 publications
0
71
0
Order By: Relevance
“…Thus, the improved SNR may be an important factor leading to a better performance in our method. Moreover, the filter (kernel) length of the convolutional layers in the proposed SDGAN and classifier (i.e., 32) is larger than those in existing DLbased methods [17], [18] (i.e., 10 and 20). Typically, a larger filter length means a better frequency response, so the convolutional layers in the proposed networks may extract better features for detection.…”
Section: ) Performance Comparisonmentioning
confidence: 98%
“…Thus, the improved SNR may be an important factor leading to a better performance in our method. Moreover, the filter (kernel) length of the convolutional layers in the proposed SDGAN and classifier (i.e., 32) is larger than those in existing DLbased methods [17], [18] (i.e., 10 and 20). Typically, a larger filter length means a better frequency response, so the convolutional layers in the proposed networks may extract better features for detection.…”
Section: ) Performance Comparisonmentioning
confidence: 98%
“…Table 3. The results of the proposed system out performs all other algorithms presented in [23][24][25].…”
Section: Confusion Matrixmentioning
confidence: 99%
“…In [15], the machine learning algorithms were demonstrated that appreciably outperform classical signal detection methods in the 3.5-GHz band. Furthermore, Gao et al [16] proposed a deep learning-based signal detector that exploits the underlying structural information of the modulated signals. Peng et al [17] explored the transfer learning to address robustness in DL-based spectrum sensing to improve the robustness.…”
Section: A Supervised Learning-based Mac Designmentioning
confidence: 99%
“…Substituting (9) and (12) into (8), the achieved throughput with inference errors is calculated as (15), as shown at the bottom of this page. Then, by substituting (15) into 7, the system throughput can be achieved as (16), as shown at the bottom of this page, where γ denotes the inference error rate and α is the probability that over-estimation occurs.…”
Section: ) Case 1: Over-estimationmentioning
confidence: 99%